Case report: A late and isolated presentation of meningoencephalomyelitis uncovers a novel pathogenic variant in the CIITA gene - Alosaimi, Mohammed F.; Hamad, Muddathir H.; AlShammari, Muneera J.; Jamjoom, Dima Z.; Musibeeh, Najd S. (Frontiers in Pediatrics, 2023)
Background: Bare lymphocyte syndrome type II (BLS II) is a rare form of severe combined immunodeficiency caused by mutations in CIITA gene which regulate major histocompatibility complex class II (MHC II) expression.Objective: To report a Saudi boy with a novel mutation in CIITA gene who presented late with acute meningoencephalomyelitis resulting in severe neurodevelopmental regression.Methods: By reviewing the patient's clinical and laboratory data obtained from medical records and performing literature search BLS II.The patient presented with acute meningoencephalomyelitis confirmed by MRI finding and later was found to carry a homozygous pathogenic variant in CIITA gene p.(Leu473Hisfs*15). The patient has absent MCH II expression confirming the genetic diagnosis of autosomal recessive BLS II. Surprisingly, patient's prior clinical history was unremarkable for significant infections or autoimmunity.We are reporting a case with novel CIITA gene mutation, presenting atypically with late and isolated severe infection. Isolated severe meningoencephalomyelitis could be a manifestation of primary immunodeficiency.